2018
DOI: 10.1002/jsfa.9243
|View full text |Cite
|
Sign up to set email alerts
|

Uniconazole and diethyl aminoethyl hexanoate increase soybean pod setting and yield by regulating sucrose and starch content

Abstract: S3307 and DA-6 promoted the accumulation and availability of sucrose and starch content in source organs and increased sucrose and starch content in flowers and pods or seeds, thereby maintaining the balance between source and sink organs and contributing to increased pod setting rates and soybean yield. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 38 publications
5
27
0
3
Order By: Relevance
“…The results were consistent with the findings (Liu et al, 2019;Mei et al, 2014;Qiu, Wang, Yan, & Jin, 2005). The results were consistent with the findings (Liu et al, 2019;Mei et al, 2014;Qiu, Wang, Yan, & Jin, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…The results were consistent with the findings (Liu et al, 2019;Mei et al, 2014;Qiu, Wang, Yan, & Jin, 2005). The results were consistent with the findings (Liu et al, 2019;Mei et al, 2014;Qiu, Wang, Yan, & Jin, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Sucrose synthase, a glycosyltransferase, can catalyze UDP-glucose to sucrose 43 . It was reported that these genes are involved in regulation of plant growth and development by providing a sustained supply of carbon 44,45 .…”
Section: Identification Of Degs In Stem Formation the Photoperiod Ofmentioning
confidence: 99%
“…Diethyl aminoethyl hexanoate (DA-6), an artificial tertiary amine, is a plant growth regulator that has been applied to many plant species, such as maize, cotton, soybean, peanut, and tomato [1–3]. Extensive studies have demonstrated that DA-6 has many beneficial effects on agricultural production, including increasing the photosynthetic rate and yields, promoting biomass accumulation, and improving germination and seedling establishment of naturally and artificially aged soybean seeds [2, 4]. Moreover, DA-6 can accelerate microalgal growth and enhance the quantity and quality of lipids for biodiesel production [5].…”
Section: Introductionmentioning
confidence: 99%
“…DA-6 has been applied at many stages, including germination, seedling growth, and flowering [1, 2]. The dissipation half-lives of DA-6 are 1.1–2.2 days, 5.4–8.2 days and 1.5–1.9 days in pakchoi, in cotton, and in the soil, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation